Analisis Potensi Erosi DAS Petapahan Pada Embung Petapahan - Hakim, Lukman Nul; Mudjiatko, Mudjiatko; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Land use change in the Petapahan Watershed will increase the flow of the surface. The surface flow will increase the amount of soil erosion and sediment transport capacity. Sediment transport will enter the Petapahan Reservoir, so that will lead to silting on thePetapahan Reservoir. It will have an impact on the function and effective life of the reservoir. The USLE method was used to estimate erosion in the Petapahan watershed. GIS was used to predict the value of USLE parameters. The result of analysis shows thatErosion occurring in Petapahan Watershed is in low grade (15 - 60 ton/ha/year) and the potential of erosion that goes to Petapahan Reservoir is 294,8287 ton/year.Keywords: land use, erosion potential, USLE, GIS